Sistem vladanja v slovenski politiki športa - Kustec Lipicer, Simona (Družboslovne razprave, 2006)
An overview of the existing academic and expert literature reveals that we cantrace many different approaches to the phenomena of governance, among them one explicitly oriented towards the field of sport. Therefore we focus our analysis mainly on the issue of (non)existence of the elements of the so-called sports governance in Slovenian sports policy. The potential presence of this concept is being tested through the analysis of historical and existing relations between the state and non-state policy players from the policy and polity-politics perspective. Regarding policy perspective we emphasise the importance of modes and approaches of legal regulation of the field, while in the polity-politics case the normatively defined roles, responsibilities and net works between the state and non-state policy players players are being outlined. Our case study indicates that the level of intensity of the analysed elements has been growing steadily over time, which can at least in principle be regarded as an indicator of growing co-operation between the state and society, and with that also of the presence of the governance idea. On the other side however this finding pensat least two fresh dilemmas. The first one concerns the question of the quality of these relations in the light of the achieved policy outcomes, while the other dilemma relates to the prospect of growing intensity of state intervention in the field of sport.
Keywords: Sport; Šport; Public policy; Javna politika; Governance; Vladanje; Civil society; Civilna družba; Modeli; Models; Slovenia; Slovenija; športna politika